The Effect of the Picture and Picture Learning Model in Increasing Students' Interest in Learning at SMP Negeri 1 Langsa - Fakhrurrazi, Fakhrurrazi; Rambe, Saparuddin; Nuraini, Nuraini (Seutia Hukamaa Cendekia, 2024)
The picture and picture learning model uses pictures and is paired or ordered into a logical order. This learning model relies on images, the main factor in the learning process. In the learning process in grade VIII, some students are not enthusiastic about participating in learning. This happens because of several things, namely the use of learning models. The use of the learning model is very important. This is where the right learning model is needed so that learning can run effectively and attract students' interest so that they can achieve optimal learning interest. Therefore, this study examines the influence of the picture and picture learning model in increasing students' interest in Islamic Religious Education subjects. This study used quantitative research on the experimental design in the experimental and control classes. The research instruments used are tests, questionnaires, and documentation. The results of the study on the effect of the use of the picture and picture learning model on students' learning interest were obtained as the average score of students' learning interest in the experimental class with a total of 25 students was 63.82, and in the control class with a total of 25 students was 56.56. Based on the hypothesis test of the student's learning interest in the experimental and control classes, the tcount > ttable was 7.094 >2.009, and the significant value was 0.00 < 0.05. Therefore, it can be concluded that using the picture and picture learning model significantly influences students' interest in PAI subjects at SMP Negeri 1 Langsa, so the data contributes well. In this study, the picture and picture learning model can increase students' interest in learning and achieve the desired learning outcomes. In the interactive learning process, students are invited to actively ask and answer questions with friends and teachers to achieve the desired learning interest using this learning model